Marketing Technologies In Educational Management: Current Problems - Гавриш, Ірина Іванівна; Зрибнєва, Ірина Павлівна; Романюк, Надія Василівна; Гордіца, Тетяна Манолівна (S International Journal of Computer Science and Network Security, VOL.22 No.10, October 2022, 2022)
The article considers in detail the possibilities and significance of marketing technologies for additional education programs as the most flexible and adaptive component of the educational process. Moreover, additional education programs are the most market-defined. Also at this stage, we have developed the structure of the e-mail message about ongoing additional educational programs in order to promote them, and on its basis, we have prepared an example of a letter for e-mail.informational and educational mailing using techniques to attract the attention of the addressee in order to promote additional educational programs.The content of the letter was also formed for students of the electronic course "Education Marketing", sent out in order to monitor the educational process.
Keywords: Keywords: higher education, education system, marketing technologies, computer technology